Economics for the curious : inside the minds of 12 Nobel Laureates - Solow, Robert M.; Murray, Janice; SpringerLink (Online service). (London : Palgrave Macmillan UK, 2014)
12 Nobel Laureates take readers on a tour of some of the everyday issues that can be explored using basic economic principles. Topics include how economic tools can be used to rebuild nations in the aftermath of a war; financing retirement as longevity increases and what governments should really be doing to boost the economy.
Keywords: Behavioral economics; Microeconomics; Macroeconomics; Economic growth; Environmental economics